APPLICATION CLUSTER ANALYSIS ON THE GOOGLE PLAY STORE USING THE K-MEANS METHOD - Hastri Cantya Danahiswari; Yovan Febriawan Nurpratama; Dhian Satria Yudha Kartika (IJCONSIST JOURNALS, 2022)
Implementation of data mining can be used to identify information that will be useful for several parties. There are various methods in data mining, one of the methods used in clusters is the K-Means algorithm. These clusters can be used for android developers in identifying what applications need to be improved and developed to make it better for android users. The results showed that there were two clusters that had different averages. The first cluster is defined as an application that is less attractive to users due to several factors, while for the second cluster it is defined as an application that the user is interested in, caused by the application offering the features that the user needs, is informative, does not require costs and can function properly.